TEMPERATURE DEPENDENT ACOUSTICAL STUDY OF THERMOPHYSICAL PROPERTIES OF BINARY MIXTURES OF DIETHYL CARBONATE + 2-METHOXYETHANOL (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of present study is to determine the internal pressure (pi), enthalpy (H), entropy (Ts), excess internal pressure (piE), excess enthalpy (HE) and excess entropy (TsE) at temperatures 303.15, 308.15, 313.15 and 318.15 K over the entire mole fraction range. The measured values of densities (r) and ultrasonic velocities (u) of (Diethyl carbonate (DEC) + 2-Methoxyethanol (2-ME)) binary mixtures have been used. The excess values are fitted to the Redlich−Kister smoothing polynomial equation to estimate the binary coefficients and standard deviation between the experimental and calculated values. The results have been discussed in terms of molecular interactions due to physical, chemical and structural effects between the unlike molecules.